Task-based bipa writing in the age of geo-spatial tools: a systematic review - Dyah Ayu Larasati; Nurul Murtadho; Radeni Sukma Indra Dewi (JL3T (Journal of Linguistics, Literature and Language Teaching), 2026)
Technology-mediated task-based language teaching is widely recognized for its potential to support second language writing through meaningful, communicatively authentic tasks. Geo-spatial applications such as Google Maps offer dynamic visual representations of space that align with functional writing tasks involving routes and navigation, yet their pedagogical integration in second language writing, particularly in Indonesian as a foreign language (Bahasa Indonesia bagi Penutur Asing, BIPA), remains largely unexplored. This systematic literature review examines research at the intersection of task-based language teaching, technology-enhanced writing, and geo-spatial tool use, with particular attention to beginner BIPA learners and direction-giving as a functional writing target. Although direction-giving writing is formally mandated as a competency at BIPA Level 1, no empirical study has investigated how it might be developed through task-based or technology-mediated instruction. Guided by the Population-Intervention-Comparison-Outcome-Context framework and a Preferred Reporting Items for Systematic Reviews and Meta-Analyses 2020 selection procedure, 84 studies were initially identified, of which 26 were included for in-depth analysis. Findings reveal three predominant strands: BIPA and second language writing studies emphasizing genre, culture, and functional literacy; task-based research reporting improvements in writing quality and learner motivation; and technology-enhanced collaborative writing employing digital platforms. Only one study explicitly integrates Google Maps, situated in an English as a foreign language recount-writing context rather than in BIPA or direction-giving instruction. The review identifies a clear gap at this intersection and proposes pedagogically grounded directions for designing geo-spatial-tool-mediated writing tasks, with Google Maps as the primary exemplar, in BIPA classrooms.